A Blind Spot? Screening for Mild Intellectual Disability and Borderline Intellectual Functioning in Admitted Psychiatric Patients: Prevalence and Associations with Coercive Measures. - Jeanet Grietje Nieuwenhuis; Eric Onno Noorthoorn; Henk Llewellyn Inge Nijman; Paul Naarding; Cornelis Lambert Mulder (PLoS ONE)
Background Failure to detect psychiatric patients' intellectual disabilities may lead to inappropriate treatment and greater use of coercive measures. Aims In this prospective dynamic cohort study we screened for intellectual disabilities in patients admitted to psychiatric wards, and investigated the use of coercive measures with these patients. Methods We used the Screener for Intelligence and Learning disabilities (SCIL) to screen patients admitted to two acute psychiatric wards, and assessed patient characteristics and coercive measures during their stay and over the last 5 years. Results Results on the SCIL suggested that 43.8% of the sample had Mild Intellectual Disability or Borderline Intellectual Functioning (MID/BIF). During their current stay and earlier stays in the previous 5 years, these patients had an increased risk of involuntary admission (OR 2.71; SD 1.28-5.70) and coercive measures (OR 3.95, SD 1.47-10.54). Conclusions This study suggests that functioning on the level of MID/BIF is very prevalent in admitted psychiatric patients and requires specific attention from mental health care staff.